Mediating Effects of Auditor Expertise on the Effect of Locus Of Control and Organizational Commitment on Auditor Performance - Iman Supriadi; Wulandari Harjanti; Rahma Ulfa Maghfiroh (Yayasan Ilomata, 2021)
The bookkeeping occupation has actually an essential function in offering dependable monetary info for the federal authorities, financiers, creditors, investors, workers, debtors, in addition to for the general public as well as various other curious celebrations. This study intends towards analyze the effect of locus of control, auditor expertise, and organizational commitment on auditor performance, towards analyze as well as evaluate whether auditor proficiency mediates the impact of locus of command as well as business dedication on auditor efficiency. This type of research is a quantitative study with a causal approach. Data collection was carried out by dispersing questionnaires straight towards auditors that operate at the Tax obligation Bookkeeping Solid in Surabaya. The results showed that locus of control had a positive effect on auditor expertise and auditor performance. The same thing happened to the organizational commitment variable. Auditor expertise has a significant effect on auditor performance and auditor expertise variable has the ability to moderate the impact of locus of command as well as business dedication on auditor efficiency. This examine shows the impact of locus of command as well as business dedication on auditor efficiency. The outcomes revealed that if the auditors have actually a higher dedication towards the company, it will result in increased performance. These findings have implications for the inculcation of organizational and professional values ​​in auditors.